2006
DOI: 10.1080/10473289.2006.10464572
|View full text |Cite
|
Sign up to set email alerts
|

Is Levoglucosan a Suitable Quantitative Tracer for Wood Burning? Comparison with Receptor Modeling on Trace Elements in Lycksele, Sweden

Abstract: Particle emissions from residential wood combustion in small communities in Northern Sweden can sometimes increase the ambient particle concentrations to levels comparable to densely trafficked streets in the center of large cities. The reason for this is the combination of increased need for domestic heating during periods of low temperatures, leading to higher emission rates, and stable meteorological conditions. In this work, the authors compare two different approaches to quantify the wood combustion contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
75
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(83 citation statements)
references
References 27 publications
(31 reference statements)
6
75
1
1
Order By: Relevance
“…The anhydrosugar was only detectable in lowtemperature samples (150e350 C), with maximum yield obtained from samples produced at 250 C, regardless of plant species. A laboratory emission study of wood and pellet boilers gave 0.3% w/w to 22% w/w levoglucosan to particle mass, indicating that the levoglucosan fraction may be highly dependent on combustion parameters, making it uncertain to use it as a quantitative tracer under real-world burning conditions (Hedberg et al, 2006). Another variable that has a strong influence on the yield of levoglucosan from cellulose is the presence of inorganic ions (Dobele et al, 2005).…”
Section: Woodstovementioning
confidence: 99%
“…The anhydrosugar was only detectable in lowtemperature samples (150e350 C), with maximum yield obtained from samples produced at 250 C, regardless of plant species. A laboratory emission study of wood and pellet boilers gave 0.3% w/w to 22% w/w levoglucosan to particle mass, indicating that the levoglucosan fraction may be highly dependent on combustion parameters, making it uncertain to use it as a quantitative tracer under real-world burning conditions (Hedberg et al, 2006). Another variable that has a strong influence on the yield of levoglucosan from cellulose is the presence of inorganic ions (Dobele et al, 2005).…”
Section: Woodstovementioning
confidence: 99%
“…Several methods have been introduced to identify and quantify OC emission sources, such as the use of organic molecular tracers (Simoneit et al, 1999), receptor models (positive matrix factorization, PMF; chemical mass balance, CMB) (Singh et al, 2017;Bove et al, 2014;Marcazzan et al, 2003), and dispersion models (Colvile et al, 2003); however, their reliability is limited by their low atmospheric lifetimes, in turn due to chemical reactivity and highly variable emission factors (Fine et al, 2001(Fine et al, , 2002(Fine et al, , 2004Gao et al, 2003;Hedberg et al, 2006;Robinson et al, 2006). Recently, radiocarbon ( 14 C) analysis has been used as a powerful tool for facilitating the direct differentiation of non-fossilfuel (NF) carbon sources from fossil fuel (FF) sources, because 14 C is completely absent from FF carbon (e.g., diesel and gasoline exhaust, coal combustion), whereas NF carbon (e.g., biomass burning, cooking and biogenic emissions) shows a high contemporary 14 C level (Szidat et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…These values are similar to average winter ambient concentrations reported for communities impacted by residential wood smoke (Bergauff, et al, 2009;Caseiro, et al, 2009) reported (Bergauff, et al, 2009;Caseiro, et al, 2009;Gorin, et al, 2006;Hedberg, et al, 2006;Yttri, et al, 2009) and Burns Lake (0.42 + 0.21 pig m" 3 ) is similar to 48-hour levoglucosan samples collected during the winter in Prince George (0.40 ± 0.30 jig m" 3 ), a city with a population of ~71,000 located 225 km west of Burns Lake (Barn, et al, 2008).…”
Section: Community-wide Representation Of Pm2 5 Teomssupporting
confidence: 85%
“…Although, its emission is inconsistent and dependent upon fuel type and combustion efficiency (larger emissions during less efficient burning) (Fine et al, 2004b;Hedberg et al, 2006). Earlier research indicated that levoglucosan is stable in the atmosphere, even when exposed to sunlight (Fraser & Lakshmanan, 2000;Simoneit & Elias, 2000).…”
Section: Chemical Tracersmentioning
confidence: 99%